London, you have a problem with women: trust towards the police in England - Pickering, Steve (Policing and society, 2024)
Following a series of high-profile incidents of violence against women by serving London Metropolitan Police Officers, questions of standards and the public’s confidence in policing are in the spotlight. Over a fifteen-month period between July 2022 and September 2023 using monthly surveys of representative English samples, this study confirms that women, in general, are more trusting in the police than men. This, however, does not hold true in London. Out of nine regions in England, London is the only region where women’s overall trust in the police is lower than men. Lower levels of trust in the police among women in London hold when controls for age, income, political environment and crime levels are considered. In line with existing literature that considers women being more sensitive to cues about trustworthiness, the concerning incidents of sexual violence by police officers against women are likely to further erode trust in police in the capital, which already ranks last among England’s nine regions in citizen trust of the police. Approval was granted for this study to be carried out by the College of Business, Arts and Social Science Research Ethics Committee, Brunel University London. Approval reference: 35290-LR-Jan/2022-37313-1.